Recent developments in lignin modification and its application in lignin‐based green composites: A review - Agustiany, Erika Ayu; Rasyidur Ridho, Muhammad; Rahmi D. N., Muslimatul; Madyaratri, Elvara Windra; Falah, Faizatul; Lubis, Muhammad Adly Rahandi; Solihat, Nissa Nurfajrin; Syamani, Firda A.; Karungamye, Petro; Sohail, Asma; Nawawi, Deded Sarip; Prianto, Arief Heru; et al. (Polymer composites, 2022)
Lignins are the most important aromatic renewable natural resource today, serving as a sustainable, environmentally acceptable alternative feedstock to fossil‐derived chemicals and polymers in a vast scope of value‐added applications. Lignin is a biopolymeric molecule that, together with cellulose, is a fundamental component of higher vascular plants structural cell walls. It can be extracted from by‐products of the pulp and paper industries, agricultural waste and residues, and biorefinery products. Lignin properties may vary depending on source and extraction method with carbon and aromatic as the main compositions in lignin structure. These rich compositions make lignin more valuable, allowing for the creation of high‐value‐added green composites. However, the complex structure of lignin creates low reactivity to interact with crosslinker, and hence chemical modification is substantial to overcome this problem. This review aimed to present and discuss lignin structure, variation of lignin chemical properties regarding its source and extraction process, recent advances in chemical modification of lignin to enhance its reactivity, and potential applications of modified lignin for manufacturing value‐added biocomposites with enhanced properties and lower environmental impact, such as food handling/packaging, seed coating, automotive devices, 3D printing, rubber industry, and wood adhesives.